Membangun Kebersamaan Pendidikan Islam dalam Keluarga di Masa Pandemi Covid 19 - Muhammad Nasir; Erlinawati Erlinawati; Muslimah Muslimah (At Turots: Jurnal Pendidikan Islam, 2022)
This study aims to find out how to build togetherness in the family during the Covid 19 pandemic. It uses a qualitative library research type method. The data sources used are secondary data sources, which are analyzed in theory from various reference sources such as articles, books and the Koran from valid sources and analyzed consistently. Research findings that building togetherness in the family is a must for a family. But to build this togetherness is not as easy as one would like, especially during the Covid-19 pandemic which was endemic in this country. There are many things that must be considered in building family togetherness, especially the importance of maintaining good communication, good cooperation and mutual respect. During the long-standing Covid-19 pandemic